FACTORS AFFECTING REAL EARNINGS MANAGEMENT - Prayitno, Veronica (Academic Research and Community Services, 2019)
The purpose of this research is to identify the influence of earnings change, debt/equity ratio, liquidity effect, growth effect, size effect, asset sale level, return on asset, market to book ratio, and board size to real earnings management. The other purpose of this research was to compare with the results of the previous research. This research used non-financial companies listed in Indonesia Stock Exchange (IDX) during the research period 2014 until 2017. Samples were collected using purposive sampling method, where 93 companies fulfill the criteria. Multiple linear regressions and hypothesis testing are used as the data analysis method in this research. The results of this research show that four variables: earnings change, debt/equity ratio, return on asset and market to book ratio statistically have effect on real earnings management, while the other five variables: liquidity effect, growth effect, size effect, asset sale level and board size statistically do not have effect on real earnings management of listed non-financial firms in Indonesia.